Chasing the rose : an adventure in the Venetian countryside - Di Robilant, Andrea, 1957- (Alfred A. Knopf, 2014)
"The author chronicles his search for a fabled antique rose--a tale that takes us back to the time of Josephine Bonaparte, and looks into the future of this much beloved flower"--